Current trends in the management of proximal humerus fractures in elderly patients - Ascani, Claudio; Scacchi, Marco; Passaretti, Daniele; Bullitta, Gianluca; De Cupis, Mauro; Calella, Piergiorgio; Bruno, Lucagiuseppe; Trombaccia, Massimiliano (Lo Scalpello - Journal, 2021)
Proximal humeral fractures are among the most common fractures in the elderly. Along with the increasing life expectancy of the Western population, the incidence of these fractures is rising rapidly, with osteoporosis as an important factor, affecting mostly active persons aged 60 and older. In such patients, proximal humeral fracture can potentially affect independ- ence and deteriorate the quality of life. Currently, several options are available for the treatment of proximal humerus fractures in elderly patients. The main treatments include open reduction and internal fixation, percutaneous closed fixation, and intramedullary nailing or total shoulder arthroplasty, depending on multiple variables including patient age, comorbidities, activity level, functional demands, and goals/expectations of treatment.